2014
DOI: 10.1590/0104-530x496-13
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de fluxograma orientativo para aplicação de índices de capacidade

Abstract: This study presents a flowchart to direct the choice of control chart and capability indices for processes with response variables: (i) uncorrelated, (ii) correlated dependent control variables, and (iii) autocorrelated.The use of the flowchart was illustrated by applying it to the hard turning process of an agricultural machinery company. The process was monitored by control charts for multiple regression, and its capability was assessed using capability indices to control charts based on regression models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Control charts are the main statistical methods of SPC for analyzing data from sampling, replacing the mere detection and correction or exchange of defective products by the study and prevention of problems related to quality, aiming to prevent defective products from being produced (Souza et al, 2014). A process is under statistical control or stable when the variability is associated only with random causes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Control charts are the main statistical methods of SPC for analyzing data from sampling, replacing the mere detection and correction or exchange of defective products by the study and prevention of problems related to quality, aiming to prevent defective products from being produced (Souza et al, 2014). A process is under statistical control or stable when the variability is associated only with random causes.…”
Section: Introductionmentioning
confidence: 99%
“…For all of them, process stability and normality of the random variable are required. Souza et al (2014) reported that, depending on the index used, the conclusions about the process capability can be differentiated, demonstrating the importance of choosing appropriate capability indices according to the behavior of each process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to specialized scientific literature, studies such as those by Müller et al (2010), Carvalho et al (2013), Schwaab et al (2013), Souza et al (2014) and Schimitz et al (2014), among others, show that the use of process management methodologies is up-to-date and aims at increasing organizational performance and competitiveness.…”
Section: Introductionmentioning
confidence: 99%